T Cell Immunity to the Alkyl Hydroperoxide Reductase of Burkholderia pseudomallei: A Correlate of Disease Outcome in Acute Melioidosis - Reynolds, Catherine (J Immunol, 2015)
There is an urgent need for a better understanding of adaptive immunity to Burkholderia pseudomallei, the causative agent of melioidosis that is frequently associated with sepsis or death in patients in Southeast Asia and Northern Australia. The imperative to identify vaccine targets is driven both by the public health agenda in these regions and biological threat concerns. In several intracellular bacterial pathogens, alkyl hydroperoxidase reductases are upregulated as part of the response to host oxidative stress, and they can stimulate strong adaptive immunity. We show that alkyl hydroperoxidase reductase (AhpC) of B. pseudomallei is strongly immunogenic for T cells of ‘humanized’ HLA transgenic mice and seropositive human donors. Some T cell epitopes, such as p6, are able to bind diverse HLA class II heterodimers and stimulate strong T cell immunity in mice and humans. Importantly, patients with acute melioidosis who survive infection show stronger T cell responses to AhpC relative to those who do not. Although the sequence of AhpC is virtually invariant among global B. pseudomallei clinical isolates, a Cambodian isolate varies only in C-terminal truncation of the p6 T cell epitope, raising the possibility of selection by host immunity. This variant peptide is virtually unable to stimulate T cell immunity. For an infection in which there has been debate about centrality of T cell immunity in defense, these observations support a role for T cell immunity to AhpC in disease protection.